The predictive value of the ultrasound grayscale ratio for identifying malignant thyroid nodules - Lian, Kaimei; Lin, Teng (Frontiers in Endocrinology, 2025)
PurposeTo assess the clinical utility of ultrasound grayscale ratio (UGSR) in distinguishing between benign and malignant thyroid nodules.MethodsWe conducted a retrospective analysis of patients diagnosed with thyroid nodules between January 2017 and December 2021. Malignancy and benignity were determined based on histopathology (biopsy or surgery) as the reference standard. Conventional ultrasonography (US) was performed to measure the maximum diameter of each nodule and assess positive features of the Chinese Thyroid Imaging Reporting and Data System (C-TIRADS). UGSR was calculated as the ratio of nodule grayscale value to surrounding thyroid parenchyma grayscale value, quantified using ImageJ software. Two experienced radiologists used ImageJ software for UGSR measurements. Logistic regression analysis examined the association between UGSR and thyroid malignancy. A receiver operating characteristic (ROC) curve analysis was conducted, and the area under the curve (AUC) was calculated to assess UGSR’s effectiveness in distinguishing between benign and malignant thyroid nodules. The UGSR cut-off value was established through ROC curve analysis.ResultsA total of 125 nodules (78 benign, 47 malignant) were evaluated. Significant differences were observed between benign and malignant nodules in maximum diameter (p = 0.042), UGSR (p < 0.001), and C-TIRADS features (p < 0.001), supporting UGSR’s diagnostic utility. However, no significant intergroup differences were observed in gender or age distribution (p>0.05 for both). Multivariable logistic regression analysis identified UGSR, irregular margins, taller-than-wide orientation, and microcalcifications as independent predictive factors for differentiating malignant from benign thyroid nodules (all p<0.05). The diagnostic performance evaluation demonstrated that UGSR achieved an AUC of 0.852 (95% CI: 0.792 - 0.912), with a sensitivity of 63.83% and specificity of 92.31%. UGSR showed significantly superior diagnostic accuracy compared to markedly hypoechogenicity (p<0.05).ConclusionUGSR demonstrated high specificity (92.31%) and reliability in differentiating malignant from benign thyroid nodules, suggesting its potential as a quantitative adjunct to ultrasound diagnosis, though sensitivity (63.83%) warrants combination with other features.